Hubungan Sikap Ibu dengan Kepatuhan Kunjungan ke Posyandu Balita di Wilayah Kerja Pustu Bajuh Kecamatan Kapuas Tengah - Irasantaliana; Carolin, Putria; Frisilia, Melisa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Posyandu is a form of community-based health effort that is managed and organized by, by, for and with the community. Compliance with visits to posyandu for toddlers is still low, which is a problem that hampers the implementation of health services through posyandu. Factors that influence low compliance are knowledge, work and attitudes of mothers of toddlers. At the research site, community participation in coming to the posyandu was 37.1%. This data is below the target of the Kapuas District Health Service, namely 80%.Objectivethe research is to determine the relationship between maternal attitudes and compliance with visits to posyandu for toddlers in the work area of Pustu Bajuh, Central Kapuas District, Kapuas Regency.This type of research is correlational with a cross-sectional approach. This research was conducted on January 15-21 2024. The population in this study was 100 respondents with a sample size based on calculation results of 70 respondents. The sampling technique is purposive sampling. The instruments used were questionnaires and observation sheets. The data analysis used was the chi square test.Resultsthe study found that 30 (43%) had sufficient attitudes and 45 (64%) were disobedient. The p value is 0.018 < 0.05, which means that there is a relationship between mother’s attitude and compliance with visits to the posyandu for toddlers in the work area of Pustu Bajuh, Central Kapuas District, Kapuas Regency.It is hoped that the results of this research can improve mothers’ attitudes towards the benefits of posyandu, mothers increase compliance with visits to posyandu to monitor toddler growth and toddler nutritional status. Villages can collaborate across sectors to motivate mothers of toddlers to do posyandu and community health centers can provide outreach using posters/leaflets as reading material.